(untitled) (London Journal of Research In Humanities and Social Sciences, 2026)
In the 1990s supporters of economic freedom had reasons to be optimistic. Because of its economic superiority the West had just won the Cold War. The Soviet Union and its empire were dissolved. The threat of nuclear war and mutual assured destruction had receded. Western economic superiority was ultimately rooted in economic freedom and decentralized decision-making. As Mises (1922/1988) and Hayek (1945) had recognized, private property rights in the means of production and decentralized decision-making are essential, if we want to benefit from of a rational allocation of scarce resources and to exploit human knowledge which is dispersed across millions of minds. Decentralized decision-making is maximized in market economies with limited government where consumers rule and people enjoy entrepreneurial freedom. It is minimized in centrally planned economies.